Assessing the prevalence and risk factors associated with Entamoeba complex infection among the Orang Asli school children in Perak, Malaysia through molecular approach. (December 2022) - Tokijoh, Nur Insyirah; Bakar, Adibah Abu; Othman, Nurulhasanah; Noordin, Rahmah; Saidin, Syazwan
Abstract: This study performed a cross-sectional investigation on the prevalence of Entamoeba complex infection comprising Entamoeba histolytica, Entamoeba dispar, and Entamoeba moshkovskii and their associated risk factors among the Orang Asli school children in three districts in Perak, Malaysia. Stool samples collected from 544 school children aged between 7 and 12 years old were examined through the nested multiplex PCR assay. The univariate and multivariate regression analyses were then carried out to determine the risk factor associated with Entamoeba complex infection. The overall prevalence of Entamoeba complex infections ( E. histolytica, E . dispar and E. moshkovskii ) was 21.3% (116/544). Most positive school children were infected with E. moshkovskii (10.7%; 58/544), followed by E. dispar (9.0%; 49/544) and E. histolytica (5.0%; 27/544). Not washing their hands after using the toilet was identified as the only significant risk factor for E. histolytica . The significant risk factors associated with E. moshkovskii infection included children within the age of 10–12 years old, with high BMI, living with working and non-educated mothers, no toilet in the house, not washing their hands after using the toilet, and fever. On the other hand, drinking water from the river, well, and rain was associated with a decreased risk of E. dispar infection . In conclusion, this study showed a high prevalence of Entamoeba spp. infections among the Orang Asli school children in Perak, Malaysia. Addressing the identified risk factors coupled with a holistic approach in breaking the transmission of Entamoeba complex can help improve their quality of life. Graphical abstract: Unlabelled Image Highlights: First study on the molecular prevalence of Entamoeba complex infection among Orang Asli school children in southern Perak. A high prevalence of Entamoeba complex was found (21.3%), with E. moshkovskii being the most predominant species (10.7%). Eight variables were considered the risk factors for Entamoeba spp. infection among this population. This study provides necessary information for designing prevention and control strategies for school and parent to reduce the burden of these Entamoeba spp. infection, especially children.